New species and new records of the family Ectopsocidae (Psocodea: ‘Psocoptera’) from India - Ramesh, Gurusamy; Babu, Rajappa; Subramanian, Kumarapuram A. (Zootaxa, 2026)
Three new species of the genus Ectopsocus, namely E. bispinosus sp. nov., E. cluniatoides sp. nov., and E. sengaltheri sp. nov., are described and illustrated. In addition, four species of Ectopsocus, (E. ewarti Vaughan, Thornton & New, 1989; E. himalayanus New, 1971; E. hypandrus Thornton, 1984; and E. meridionalis Ribaga, 1904), and one species of Ectopsocopsis (E. mozambica (Badonnel, 1931)), are reported for the first time from India. Moreover, the female of E. himalayanus New, 1971, is described for the first time. This study is the first record of the genus Ectopsocopsis from India. We also provide an updated key to the species of the family Ectopsocidae from India.